ISLAMIC BANKING IN THE WEST : THE NEED FOR ISLAMIC BANKING IN THE UK - Jehad Alowd; Astede Wodie (Universitas Trisakti, 2013)
The Islamic banking system has gained momentum worldwide. The last two decades have witnessed the emergence of Islamic banking as a viable banking system. This study is designed to investigate the awareness, needs, and motives of Muslims towards Islamic Banking in the UK. The objectives of the study are as follow; to find out the motives and needs of Muslims in the UK towards Islamic banking, to test Muslim's attitudes towards some of the principles of Islamic banking, and to find out the level of awareness in Muslim people in the UK about Islamic banking terms. A sample 300 respondents took place in this study. The study shows that Muslims in the UK were not aware of the basic Islamic financial terms and principles. The results showed the interest of Muslims in the UK to use Islamic banking; mainly their decisions were based on religious purposes. Nevertheless, Islamic banking is growing and the services available now will be expanded in the near future Keywords: Islamic Banking, UK, motives, awareness.